LincRNA‐p21 suppresses development of human prostate cancer through inhibition of PKM2. (9th October 2017) - Wang, Xiaohai; Xu, Yongzhi; Wang, Xingjie; Jiang, Chenyi; Han, Sha; Dong, Kai; Shen, Mengjun; Xu, Dongliang
Abstract: Objectives: Previously, we found that long intergenic non‐coding RNA‐p21 (lincRNA‐p21) inhibited the development of human prostate cancer. However, the underlying molecular mechanisms are poorly understood. Here, we attempted to investigate the downstream targets of lincRNA‐p21 in prostate cancer. Materials and methods: Expression of lincRNA‐p21 and PKM2 was determined by qRT‐PCR and Western blot. Lentivirus expressing shPKM2 or shCtrl was used to explore the role of PKM2 on the enhanced cell proliferation and glycolysis of lincRNA‐p21‐silenced prostate cancer cells. A xenograft mouse model was performed to investigate the effect of PKM2 suppression, glycolytic or mammalian target of rapamycin (mTOR) inhibitor on the tumorigenic capacity of lincRNA‐p21‐silenced prostate cancer cells. Results: We revealed that lincRNA‐p21 silencing in DU145 and LNCaP cells induced up‐regulation of PKM2 and activation of glycolysis, which could be reversed by PKM2 knockdown or rapamycin treatment. We also found that the proliferation and tumorigenesis of lincRNA‐p21‐silenced prostate cancer cells were significantly inhibited after knocking down PKM2. 3‐bromopyruvate (3‐Brpa) or rapamycin treatment largely decreased the tumour burden. Importantly, PKM2 expression was inversely correlated with the lincRNA‐p21 level and the survival of prostate cancer patients. Conclusions: We demonstrated that lincRNA‐p21 blunted the prostate cancer cell proliferation and tumorigenic capacity through down‐regulation of PKM2. Therefore, targeting PKM2 or glycolysis might be a therapeutic strategy in prostate cancer patients with lowly expressed lincRNA‐p21.